Design and fabricate smart laundry cart - Aneth Athea, Mat Som (2010)
Musculoskeletal injury risk factors associated with pushing and pulling of loads. The most common cause of musculoskeletal injury is a combination of physical overloads created by overtraining or by the repetitive use of a joint or a particular muscle group. The field of invention relates to a cart structure, and more particularly pertains to a new and improved multipurpose laundry cart which is arranged for the support and transport of various laundry stations. Many laundry cart apparatus of various types have been utilized in the prior art. However, they fail to provide the necessary multiple laundry work stations, ease of assembly, storage and mobility with appropriate ergonomic factors that can reduce MSI or musculoskeletal injury. It is an object of the present invention to provide a multipurpose laundry cart which fulfills these needs especially in reducing the factors of any injury causes. A light weight easily constructed multipurpose laundry cart which is constructed of aluminum sheets and horizontal tubular aluminum provides supports hanging or clothes therein and further provides stacking and sorted shelves compartment. The horizontal bars are for hanging such clothes and the top of the cart can be used as a platform for ironing process. Wheels are attached for mobility purpose and a special compartment is featured to keep iron in fixed position. The height of the laundry cart was constructed to avoid the MSI from occurring. Suitable height was constructed for various users play a major role in the factors of MSI and determination of suitable height was based on the common height of Malaysians citizens. In future advance of engineering, development of physical properties of tools should be better and more advance and focusing in health aspects.